Correlation of blood muscle strength and waist flexibility to students’ roundhouse kick skills in Putera Sekar (Pencak Silat) academy - Muhammad Anwarudin; Muhammad Iqbal; Tri Bayu Norito (ETUDE: Journal of Educational Research, 2020)
Background: Many fighters are not maximal in doing roundhouse kick, resulting in losses including causing injuries during the match, wasting energy because the shot that is shot does not hit the target. Purpose: The aim of this study is know what extent the relationship between the explosive power of the leg muscles and the flexibility of the waist muscles on the skill of the roundhouse kick in the athletes of the Putera Sekar Kolat Tanah Abang Pencak Silat College. Design and methods: This study used a correlation study method by examining the relationship between the explosive power of the leg muscles and the flexibility of the waist to the roundhouse kick skill. The samples in this study were 20 athletes who were still active in routine extracurricular activities. To process the required data from the flexibility test results (X1), anxiety test results (X2), and the scoring results of archery athletes, regression and correlation analysis techniques are used. Results: There is a positive relationship between leg muscle explosive power and waist flexibility on roundhouse kick skill. According to the regression correlation analysis, it was obtained that the value of Fcount was 1.973 more than Ftable 3.59 and a significant value of 0.00 less than 0.05.